A theorem of cosmic censorship: A necessary and sufficient condition for future asymptotic predictability - Newman, Richard P. A. C. (General relativity and gravitation, 1984)
Theorems are established concerning weakly asymptotically simple and empty space-times which satisfy the null convergence and generic conditions and provide necessary and sufficient conditions for such space-times to be subject to cosmic censorship in the form of future asymptotic predictability. They show that if future asymptotic predictability is violated, there exist accessible naked singularities arbitrarily far in the future and outside the event horizon for which the surrounding curvature fails to attain certain finite bounds.